PENGEMBANGAN BUDIDAYA RUMPUT UNGGUL MENGGUNAKAN FUNGI MIKORIZA ARBUSKULA SEBAGAI PAKAN SAPI POTONG DI PARAK KARAKAH KOTA PADANG - Ferry Lismanto Syaiful; Suyitman Suyitman; Evitayani Evitayani; Khasrad Khasrad; Endang Purwati (Jurnal Hilirisasi IPTEKS, 2019)
One of the most critical factors in increasing beef cattle is feed. Besides, breeders also need practical, quality, and continuous cattle feed. We need the development of superior grass technology/king grass using the arbuscular Mycorrhizal fungi to support feed production for beef cattle. The arbuscular mycorrhizal fungi play a role in increasing plant growth and resistance to attack by root pathogens and resistance to stress conditions. The objectives of this activity are: 1. to improve breeders' knowledge and skills in useful and profitable beef cattle cultivation; 2. to increase farmer's knowledge and skills in cultivating superior grass with arbuscular mycorrhizae. The method used is the counseling method, where previously through an approach, counseling, training and coaching, and finally, evaluation and monitoring. While the activities include good and profitable beef cattle cultivation and superior grass cultivation using the arbuscular mycorrhizal fungi. The partners of this activity are the Kubu Sepakat livestock group and the Parak Karakah community, Padang. Partners' problems are 1. breeders have difficulty providing forage feed, 2—lack of knowledge on good and profitable beef cattle cultivation. The activity results found that breeders increased their knowledge about excellent and profitable beef cattle cultivation techniques. From the results of the activity, it can be seen that the livestock's ability to cultivate superior grass using the arbuscular Mycorrhizal fungi has increased so that the nutritional needs of livestock can be met. Based on the results of the statistical tests that the activities carried out have an index value of 90, this indicates that the activities carried out are beneficial or successful in transferring knowledge and skills to breeders.